Changes in the Soil Fungal Community Mediated by a Peganum harmala Allelochemical - Shi, Kai; Shao, Hua (Frontiers in Microbiology, 2022)
Plants can release phytotoxic allelochemicals into the environment, not only to suppress other plants’ growth, but also alter community structure of soil microbiota, however the mechanism are often complicated. We designed a consecutive cultivation procedure to evaluate the allelopathic effect of harmaline, the major active allelochemical produced by the desert plant Peganum harmala, on soil microorganisms. Harmaline was added to the soil at 20 µg/g, and after 5 generations of cultivation, the Chao1, Pielou, Shannon and Simpon indexes changed significantly. In particular, the relative abundances of the dominant fungi, Alternaria sp. and Fusarium sp., declined drastically by 84.90% and 91.90%, respectively. Further in vitro bioassays confirmed that harmaline indeed suppressed growth of 6 Alternaria and Fusarium strains isolated from P. harmala rhizosphere soil. We thus suspect that P. harmala might produce harmaline as an effective carry-on pesticide to defend against general pathogens such as Alternaria sp. and Fusarium sp. and favor itself. Our consecutive cultivation procedure has successfully magnified the core signals from the chaotic data, implying that it can be applied to measure the effects of other allelochemicals on soil microbiota.